2001
DOI: 10.1002/jso.1105
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography monitoring for laser surgery of laryngeal carcinoma

Abstract: OCT is promising to become a new diagnosing method of laryngeal carcinoma and a tool for laser treatment monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 16 publications
(8 reference statements)
0
65
0
2
Order By: Relevance
“…Development of scanning catheters has enabled endoscopic OCT imaging of internal organs and extended the OCT study field further [9,10]. Endoscopic OCT imaging has demonstrated its ability to resolve layered tissue structures, and to differentiate normal from certain pathologic conditions within the esophagus [11][12][13][14][15][16], coronary artery [17][18][19] and other internal organs such as the oral cavity [20], larynx [21][22][23], and bladder [24].…”
Section: Introductionmentioning
confidence: 99%
“…Development of scanning catheters has enabled endoscopic OCT imaging of internal organs and extended the OCT study field further [9,10]. Endoscopic OCT imaging has demonstrated its ability to resolve layered tissue structures, and to differentiate normal from certain pathologic conditions within the esophagus [11][12][13][14][15][16], coronary artery [17][18][19] and other internal organs such as the oral cavity [20], larynx [21][22][23], and bladder [24].…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of OCT guidance and monitoring of laser surgery was first explored in the late 1990's [53,72], and subsequent studies demonstrated the ability of OCT to monitor structural alterations following prostate tissue ablation in vitro [147] and laser treatment of laryngeal carcinoma surgery [148]. More recently, Palanker et al in 2010 demonstrated a spectraldomain OCT system incorporated into a femtosecond laser module for human cataract surgery [73] (Fig.…”
Section: Oct-guided Laser Surgerymentioning
confidence: 99%
“…The biotissue is heated by the laser radiation and moved apart by the silica core of the optical¯ber. 10 The silica core is su±ciently transparent in the near IR region and is mechanically strong enough to stand the high temperatures arising at the tip of the optical¯ber tip during biotissue resection. The strongly absorbing layer at the tip of the¯ber (according to the work of Amzayyb 11 the absorption of the layer can achieve 50%) results in heating of the silica core to temperatures higher than carbonization temperature and facilitates carbon formation during biotissue dissociation resulting from the joint action of radiation and the high temperatures near the heated silica¯ber.…”
Section: Introductionmentioning
confidence: 99%